Tunable magnetic properties in tetragonal Mn-Fe-Ga Heusler films with perpendicular anisotropy for spintronics applications - Kalache, Adel; Selle, Susanne; Schnelle, Walter; Fecher, Gerhard H.; Hoeche, Thomas; Felser, Claudia; Markou, Anastasios (Physical Review Materials, 2018)
High perpendicular magnetic anisotropy is essential for the development of high-efficiency spintronics devices. In this paper, we investigate the structural and magnetic properties of Mn-Fe-Ga Heusler thin films with perpendicular magnetic anisotropy inherent to the tetragonal D022 structure. High quality films were heteroepitaxially grown on SrTiO3 substrates by magnetron sputtering technique. The magnetic properties such as saturation magnetization and coercive field are easily tunable by the variation of the Mn/Fe ratio, while retaining out-of-plane magnetization over large composition range. The uniaxial anisotropy was improved in Mn2.6-xFexGa1.4 through Fe substitution at a fixed Ga excess. Films with composition Mn1.6Fe1Ga1.4 were found to be stable down to a thickness of 10 nm. Transmission electron microscopy investigations proved the high quality of the films as well as chemical homogeneity. The Hall effect exhibits an anomalous contribution that dominates over the normal part, leading to Hall angle as high as 3.4%. These findings suggest great potential for the integration of tetragonal Heusler materials into spintronic devices.
CRIS-Team Scopus Importer:2022-04-14